2014
DOI: 10.1111/jocn.12676
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of factors that impact patients’ subjective experience of nurse‐led clinics: a qualitative systematic review

Abstract: Knowledge of patients' feelings and the importance of person-centred, individualised care may contribute to development of future training and re-training programs in basic nursing skills. This is significant in that it contributes to future positive patient experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 42 publications
5
35
0
Order By: Relevance
“…Our qualitative analysis revealed similar findings as previous studies 5 , 7 , 9 , 24 . Patients believed that NRP might reduce physician workload and that doctors and nurses should communicate adequately and share responsibility.…”
Section: Discussionsupporting
confidence: 91%
“…Our qualitative analysis revealed similar findings as previous studies 5 , 7 , 9 , 24 . Patients believed that NRP might reduce physician workload and that doctors and nurses should communicate adequately and share responsibility.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous research showing that an NLC leads to fewer additional contacts with healthcare services [ 26 ]. PCC increases patients’ confidence in their own ability and patients become autonomous and independent [ 27 ]. Research has shown that PCC in various fields of inpatient care has led to a reduction in the length of the hospital stay by up to 70 % and reduced costs without a negative impact on health-related quality of life [ 12 , 13 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jakimowicz et al . () found evidence that positive patient experiences in nurse‐led clinics were related to good therapeutic relationships, effective communication and collaboration and clinical skills, all of which mapped closely to Kitson et al . 's () patient‐centred framework, or McCormack and McCance's () person‐centred nursing framework.…”
Section: Introductionmentioning
confidence: 67%